High-frequency monitoring of diet quality in Guatemala - Ramos, Gresia Dalal; Lizarazo, Miguel; Jimenez, Daniel; Bonilla, Melissa; Manners, Rhys; Martinez, Jesus David (2024)
Since 2023, an innovative system for monitoring diet quality has been implemented through pilot projects in Guatemala's eastern region, using the MEMO platform by MrBot Solutions. In 2024, the monitoring system expanded to the eastern, western, and central regions of the country, supported by local partners such as ASORECH, Cáritas Zacapa, CUNORI, CUNZAC, CUNOROC, INTECAP, CDRO, Global Communities, and the Acción Cristiana church. During implementation, variability in participant response rates was observed, influenced by factors such as distrust of receiving messages from unknown numbers via WhatsApp and limited internet connectivity. The results show that participants from Jocotán, Chiquimula, and Zacapa in the eastern region, Guatemala City in the central region, and the municipalities of Nebaj, Chiantla, San Idelfonso Ixtahuacán, and Aguacatán in the western region, had a Diet Quality Score (DQS) below 10, indicating they do not meet the recommendations for a healthy diet. These findings highlight the importance of strengthening the monitoring system by expanding the target population and diversifying incentives for participants. In this way, the system will become more robust, providing valuable information to local stakeholders for informed decision-making that promotes and strengthens food security, scaling its impact at the national level.